PENGARUH TERPAAN IKLAN RUANGGURU DI TELEVISI TERHADAP KEPUTUSAN PENGGUNAAN BIMBINGAN BELAJAR ONLINE RUANGGURU (Survei Pada Pengikut Akun Instagram @Ruangguru) - Fitriyah, (2021)
Ruangguru as one of the online tutoring service providers is known to be quite active in promoting it through advertisements on television media. Based on the existing phenomena, the existence of television media has begun to be shifted by the emergence of the internet and social media. In particular, young people who are known to spend more time on the internet and social media than on television media. However, Ruangguru, whose own target is young people or school students, continues to use television as an advertising medium and even advertises quite often on television media. Therefore, this study intends to determine whether there is an influence and how much influence the Ruangguru advertisement on television has on the decision to use Ruangguru's online tutoring. This study uses a quantitative approach with the type of explanatory research. Through the results of the correlation test, it is known that the correlation value is 0.762, which means that the relationship between variables has a strong relationship. In the results of the regression test, it is known that the two variables have a positive relationship. It was also found that exposure to television advertisements influenced the purchasing decision of Ruangguru's online tutoring, which was determined through the results of the T-test. It is also known that based on the results of a determination test of 58.1% the influence given by exposure to Ruangguru's advertisements on television on the decision to use Ruangguru's online tutoring. So from these results it can be concluded that exposure to advertising in television media can influence individuals in making a purchasing decision on Ruangguru's online tutoring as described in the principle of Selective Influence theory, namely the principle of Selective Action.